Kidd blood group allele frequencies in thai blood donors - Anan Sudkaew (2018)
We present Kidd blood group allele frequencies in Thai blood donors and compare them with other frequencies for other populations previously reported. Methods: Eight hundred blood samples obtained from 500 central Thais and 300 northern Thais were genotyped by allele specific-PCR. Results: It was found that JK * 01 and JK * 02 allele frequencies were 0.503 and 0.497 in central Thais, while the frequencies were 0.498 and 0.502 in northern Thais. The JK * 01 and JK * 02 allele frequencies in Thais were similar to those in Chinese populations, whereas the frequencies were significantly different from Japanese, French Basques, and African-Americans. Conclusions: This is the first to report of Kidd blood group allele frequencies in Thais, which is beneficial for the prevention of both alloimmunization and adverse transfusion reactions.